Upwelling of Atlantic Water in Barrow Canyon, Chukchi Sea. Issue 3 (7th March 2022) - Li, Shutong; Lin, Peigen; Dou, Tingfeng; Xiao, Cunde; Itoh, Motoyo; Kikuchi, Takashi; Qin, Dahe
Abstract: Using long‐term moorings data together with wind and sea ice measurements, we document the characteristics and variations of upwelling in Barrow Canyon and investigate the upwelled Atlantic Water (AW) on the Chukchi Sea shelf and how it impacts the ice cover. Driven by strong northeasterly winds, upwelling occurs more often in the cold months, and the occurrence tends to increase interannually since 2001. Over the 12‐year mooring record at the mouth of Barrow Canyon, roughly 10% of the upwelling events can drive AW onto the Chukchi Sea shelf. Both AW and non‐AW upwelling events have more occurrence and stronger strength in the cold months, but do not present a significant interannual trend. These variations are associated with the northeasterly winds. Comparing to the non‐AW upwelling, the AW upwelling is generally characterized by more vertical displacement of the AW layer at the mouth of Barrow Canyon, and stronger up‐canyon volume and heat transport. In the ice‐covered period, these two types of upwelling have different consequences for forming polynyas on the shelf. Under similar wind forcing, the ice reduction appears confined in the coastal region in the non‐AW upwelling events, while during AW upwelling events, the sea ice declines dramatically in the shelf interior with 15% more ice loss. It elucidates that the heat carried by the upwelled AW plays a considerable role in modulating the ice cover in the shelf interior. Plain Language Summary: Upwelling in Barrow Canyon brings heat and nutrients that can affect sea ice condition and ecosystems on the Chukchi Sea shelf. In this study, we use mooring data in the vicinity of Barrow Canyon together with the wind data and satellite ice concentration data, to investigate the characteristics and variations of upwelling in the canyon, and how the upwelled warm Atlantic Water (AW) modulates the ice cover on the shelf. Driven by the strong northeasterly winds, the upwelling in the canyon is characterized by an up‐canyon flow and uplifting of water masses, and the upwelling occurrence varies seasonally and interannually. Roughly 10% of the events can upwell the AW onto the Chukchi Sea shelf, which mainly occur in the cold months when the strong northeasterly winds blow. Under similar wind forcing, upwelling of AW leads to the significant ice decrease in the shelf interior, while non‐AW upwelling causes less ice loss that is confined along the coastal region. These discrepancies suggest that the extra heat brought by the AW upwelling in the Barrow Canyon can result in a significant ice loss in the interior of the Chukchi Sea shelf. Key Points: Driven by strong northeasterly winds, upwelling in Barrow Canyon is characterized by up‐canyon flow and vertically uplifted isopycnals Upwelling of Atlantic Water onto the Chukchi shelf mainly occurs in the cold months when extreme northeasterly wind blows Heat flux from Atlantic Water upwelling plays an important role in the sea ice loss in the Chukchi shelf interior